(untitled) (Світ фінансів, 2017)
Білик І. В. Особливості структури та інфраструктури страхових ринків України та Польщі. Розглянуто структуру страхового ринку Польщі, розкрито чинники, які вплинули на її формування, а також представлено елементи його інфраструктури у порівнянні з страховим ринком України. Обґрунтовано низку пропозицій щодо удосконалення інституційної будови вітчизняного страхового ринку. Bilyk I. Peculiarities of structure and infrastructure of insurance markets in Ukraine and Poland. The structure of Polish insurance market and factors, which influence on its formulation are examined in the article. The elements of its infrastructure comparing with analysis of Ukrainian insurance market structures are presented. The certain proposals for the improvement of the institutional structure of the domestic insurance market are proved.